The Compatibility of English Textbook for High School Level and Textbook Evaluation Aspects - Diko Putri, Syifa Mutiara; Titie, Riskie Laras; Lestari, Rizky Purwa; Ikaningrum, Rini Estiyowati (Faculty of Education and Teachers Training, 2024)
Textbooks serve as one of the useful teaching materials in a curriculum. This paper is aimed to find out that the quality of an English textbook meets the textbook evaluation aspects according to Badan Standar Nasional Pendidikan (BSNP) also experts, namely Cunningsworth (1995), and Harmer (2007). This analysis is conducted through (1) reviewing the whole content of English textbook, (2) selecting the aspects to be evaluated, (3) collecting data by analyzing the aspects of content, language, presentation, and graphics based on the developed checklist instrument, also (4) making summaries to draw the conclusion. The data analysis uses three steps, i.e. analyzing the book, describing the result whether it matches with the criteria or not, and calculating the result. The result finds that the textbook is categorized ‘excellent’.